Packaging Innovation and Selling Performance in Microenterprises: Role of Digital Marketing Training - Pranowo, Agus Setyo; Herdiyana, Herdiyana; Muharram, Hari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Micro-enterprises in Indonesia need help due to their smaller scale and limited resources, impacting their selling performance. This study explores the role of digital marketing training in boosting the selling performance of micro-enterprises through packaging innovation. This study is quantitative research, and we surveyed 383 micro-enterprises fostered by PT Permodalan Nasional Madani (PNM) in Sukabumi Regency, West Java Province. The collected data was analyzed using Partial Least Square (PLS) to see the relationship between variables. Research findings confirm the positive influence of digital marketing training on packaging innovation and selling performance, and the positive influence of packaging innovation on selling performance. Here, packaging innovation can mediate the influence of digital marketing training on selling performance. This research provides novel insights into the critical role of packaging innovation in mediating the effects of digital marketing training, highlighting the need for ongoing support and tailored training programs to boost microenterprise competitiveness and market reach. The training programs, particularly in digital marketing, can enhance the ability of packaging innovation and empower the selling performance of the micro-enterprises. The micro-enterprises need more digital training as a part of government mentoring programs, in this case by PNM.